2020
DOI: 10.1590/1983-21252020v33n317rc
|View full text |Cite
|
Sign up to set email alerts
|

Cut Cycles and Soil Carbon Potential Stocks in a Managed Forest in the Caatinga Domain in Brazil

Abstract: Management of tropical dry forests in Brazil expanded 450% in the two latest decades; but little is known about the dynamics of these areas. Thus, the objective of this work was to evaluate if the recovery of mean original biomass stocks (MOBS) is a consistent criterion to define cut cycles in a managed forest for charcoal production, and determine the remaining biomass and its contribution to soil carbon stocks. The study was conducted at the Ramalhete Settlement, in General Sampaio, CE, Brazil, in 2018. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…In the SC2 treatment, the results for 2021 exceed the 1996 data by an average of 1.4 times. This confirms the finding by Lopes et al (2020) that the original stocks of woody biomass do not correspond to the maximum potential exploitable shrub and tree biomass. In this regard, Riegelhaupt, Pareyn, and Bacalini (2010) had already questioned the exclusive use of this criterion, given, for example, the lack of parameters to certify that the initial average stock found in a certain area corresponds to the maximum stock that the site can reach.…”
Section: Structuresupporting
confidence: 90%
See 2 more Smart Citations
“…In the SC2 treatment, the results for 2021 exceed the 1996 data by an average of 1.4 times. This confirms the finding by Lopes et al (2020) that the original stocks of woody biomass do not correspond to the maximum potential exploitable shrub and tree biomass. In this regard, Riegelhaupt, Pareyn, and Bacalini (2010) had already questioned the exclusive use of this criterion, given, for example, the lack of parameters to certify that the initial average stock found in a certain area corresponds to the maximum stock that the site can reach.…”
Section: Structuresupporting
confidence: 90%
“…Evaluating an area of SDTF under management with clearcutting in Ceará, Lopes et al (2020) found that the vegetation reached the average stock of original biomass at 8 years of regeneration in a location with a hot semi-arid climate and average annual rainfall of 744 mm. However, although the initial stock was recovered seven years before the cutting cycle, the vegetation cover was still quite young, with most of the biomass occupying the first diameter class (2 -5.99 cm).…”
Section: Structurementioning
confidence: 99%
See 1 more Smart Citation
“…In sustainable forest management of the Caatinga (and other forests in Brazil), regulation by area is advocated based on the division of the forest area into annual productive units, and with a minimum harvest cycle of 15 years (Araújo Filho and Carvalho, 1997;Drumond et al, 2004;Riegelhaupt et al, 2010;Matos et al, 2019, Lopes et al, 2020. The commonly adopted cutting cycle for Caatinga forests is established by federal and state legislation, still lacking solid scientific basis.…”
Section: Introductionmentioning
confidence: 99%
“…Management of tropical dry forests in Brazil expanded 450% in the last two decades; but little is known about the ideal recovery time of the harvested stock after clear cut as well as the growth dynamics of these areas (Lopes et al, 2020). Many aspects regarding sustainability need further investigation, especially potential for recovery of productive capacity and ways to minimize anthropic impacts on vegetation.…”
Section: Introductionmentioning
confidence: 99%